2017
DOI: 10.1038/s41467-017-00383-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-large single crystals by abnormal grain growth

Abstract: Producing a single crystal is expensive because of low mass productivity. Therefore, many metallic materials are being used in polycrystalline form, even though material properties are superior in a single crystal. Here we show that an extraordinarily large Cu-Al-Mn single crystal can be obtained by abnormal grain growth (AGG) induced by simple heat treatment with high mass productivity. In AGG, the sub-boundary energy introduced by cyclic heat treatment (CHT) is dominant in the driving pressure, and the grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(88 citation statements)
references
References 40 publications
1
86
1
Order By: Relevance
“…Recently, solution‐based fabrication processes for high‐quality 2D nanostructures guided by the mechanisms of nucleation site control, epitaxial growth, and grain‐rotation‐induced coalescence have been reported as promising techniques without the needs of sophisticated equipment. By controlling their growth conditions, including chemical concentration, temperature, and solvent property, 2D metal or semimetal nanostructures can be well grown on the substrates . However, dislocations, disinclinations, and symmetry‐breaking instabilities can frequently prompt the formations of defects and grain boundaries in the synthesis processes and crystal growth rate of the 2D nanostructure is very slow …”
mentioning
confidence: 99%
“…Recently, solution‐based fabrication processes for high‐quality 2D nanostructures guided by the mechanisms of nucleation site control, epitaxial growth, and grain‐rotation‐induced coalescence have been reported as promising techniques without the needs of sophisticated equipment. By controlling their growth conditions, including chemical concentration, temperature, and solvent property, 2D metal or semimetal nanostructures can be well grown on the substrates . However, dislocations, disinclinations, and symmetry‐breaking instabilities can frequently prompt the formations of defects and grain boundaries in the synthesis processes and crystal growth rate of the 2D nanostructure is very slow …”
mentioning
confidence: 99%
“…Abnormal grain growth (AGG) can be exploited to obtain a bamboo structure or even a single crystal. It has been reported that abnormal grain growth occurs by cyclic heat treatment between the single-phase region and two-phase region in Cu-Al-Mn SMAs [71] and this simple technique has been successfully applied to obtain a large singlecrystal Cu-Al-Mn [72]. Fortunately, the Fe-Mn-Al-Ni alloy also shows the a single-phase at high temperatures and a ?…”
Section: Abnormal Grain Growthmentioning
confidence: 99%
“…Two grains are abnormally growing, and smaller grains are seen inside the surrounding grains although they exist only in a part of the abnormal grains. The smaller grains are subgrains associated with precipitation of the c phase and the sub-boundary energy is a dominant driving pressure in this AGG phenomenon [72,73].…”
Section: Abnormal Grain Growthmentioning
confidence: 99%
“…1,2 Controlled abnormal grain growth at one or several sites in the polycrystalline sample at high temperatures is also a promising methodology to grow large-sized single crystals. [3][4][5] Further, the polycrystalline to single crystal growth can be achieved without passing the material through a melting stage denoted as solid-state crystal conversion. 6 Though these methods are highly sophisticated and produce good quality single crystal materials, they are time consuming.…”
Section: Introductionmentioning
confidence: 99%